A triple trophic boost: How carbon emissions indirectly change a marine food chain. (21st January 2019) - Doubleday, Zoë A.; Nagelkerken, Ivan; Coutts, Madeleine D.; Goldenberg, Silvan U.; Connell, Sean D.
Abstract: The pervasive enrichment of CO2 in our oceans is a well‐documented stressor to marine life. Yet, there is little understanding about how CO2 affects species indirectly in naturally complex communities. Using natural CO2 vents, we investigated the indirect effects of CO2 enrichment through a marine food chain. We show how CO2 boosted the biomass of three trophic levels: from the primary producers (algae), through to their grazers (gastropods), and finally through to their predators (fish). We also found that consumption by both grazers and predators intensified under CO2 enrichment, but, ultimately, this top‐down control failed to compensate for the boosted biomass of both primary producers and herbivores (bottom‐up control). Our study suggests that indirect effects can buffer the ubiquitous and direct, negative effects of CO2 enrichment by allowing the upward propagation of resources through the food chain. Maintaining the natural complexity of food webs in our ocean communities could, therefore, help minimize the future impacts of CO2 enrichment. Abstract : Numerous laboratory experiments suggest that CO2 enrichment (or ocean acidification) will have a direct negative impact on many marine species. Using natural CO2 vents, we investigated the indirect effects of CO2 enrichment through a marine food chain. We show how CO2 actually boosted the biomass of not just primary producers (algae) and their grazers (gastropods), but also their predators (fish). In doing so, this study demonstrates how the indirect effects of CO2 enrichment can yield unexpected results and potentially buffer the negative effects of climate change.